2019
DOI: 10.3389/fimmu.2019.01620
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Phytochemical, DIM, Inhibits Proliferation, Migration, Invasion and TNF-α Induced Inflammatory Cytokine Production of Synovial Fibroblasts From Rheumatoid Arthritis Patients by Targeting MAPK and AKT/mTOR Signal Pathway

Abstract: In rheumatoid arthritis(RA) pathogenesis, activated RA fibroblast-like synoviocytes (RA-FLSs) exhibit similar proliferative features as tumor cells and subsequent erosion to cartilage will eventually lead to joint destruction. Therefore, it is imperative to search for compounds, which can effectively inhibit the abnormal activation of RA-FLSs, and retard RA progression.3′3-Diindolylmethane (DIM), the major product of the acid-catalyzed oligomerization of indole-3-carbinol from cruciferous vegetables, has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 55 publications
2
80
0
Order By: Relevance
“…In the current study, we clearly demonstrated that YAP and TAZ in RA-FLS exhibited higher expression than those in normal FLS, which was consistent with the results in multiple human cancer cells, implying that YAP and TAZ might serve function as the regulators in RA-FLS. Since RA-FLS can migrate and invade the articular cartilage and bone, thereby leading to destruction of cartilage and bone [ 6 , 7 ], we firstly established RA-FLS stable knockdown of YAP or TAZ using the lentiviral-mediated YAP or TAZ knockdown approaches to evaluate the effect of YAP or TAZ knockdown on migration and invasion of RA-FLS by wound healing and Transwell migration and invasion assays. Our data demonstrated that either knockdown of YAP or TAZ markedly decreased cell motility, indicating the role of loss of YAP or TAZ resulting in the inhibition of the aggressive invasive ability of RA-FLS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we clearly demonstrated that YAP and TAZ in RA-FLS exhibited higher expression than those in normal FLS, which was consistent with the results in multiple human cancer cells, implying that YAP and TAZ might serve function as the regulators in RA-FLS. Since RA-FLS can migrate and invade the articular cartilage and bone, thereby leading to destruction of cartilage and bone [ 6 , 7 ], we firstly established RA-FLS stable knockdown of YAP or TAZ using the lentiviral-mediated YAP or TAZ knockdown approaches to evaluate the effect of YAP or TAZ knockdown on migration and invasion of RA-FLS by wound healing and Transwell migration and invasion assays. Our data demonstrated that either knockdown of YAP or TAZ markedly decreased cell motility, indicating the role of loss of YAP or TAZ resulting in the inhibition of the aggressive invasive ability of RA-FLS.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is accumulating that the fibroblast-like synoviocytes from RA patients (RA-FLS) play a pivotal role in the pathogenesis of RA [ 1 ]. RA-FLS exhibit some tumor cell-like characteristics, such as excessive proliferation, migration, and invasion; anchorage-independent proliferation; and lack of contact inhibition in vitro [ 2 4 ], and can migrate and invade the articular cartilage and bone [ 5 ], contributing to the destruction of cartilage and bone and joint damage through secretion of proinflammation cytokines and production of the proteolytic enzymes such as matrix metalloproteinases (MMPs) [ 6 , 7 ]. Therefore, understanding and investigating the factors that regulate the migration and invasion of RA-FLS might provide novel targets for RA therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The results of clinical manifestations and pathological changes demonstrated that WJT played an important role in suppressing the pathological progression of arthritis in CIA rats, which laid a foundation for the further study. In addition, The aberrant release and recruitment of pro-in ammatory cytokines (TNF-α, IL-1β, and IL-6) are essential to the pathogenesis of RA [18,20,21]. It's well known that both TNFα and IL-1β play roles in the activation and in ltration of immune cells, and contribute to production of in ammatory cytokines and chemokines, thereby resulting in a complex network that promotes in ammatory reactions, cartilage damage and autoimmune pathology [18,22].…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by chronic inflammation, synovial hyperplasia, and bone hyperplasia and destruction [1,2]. Synoviocytes are the major cells in the synovial membrane, and these are the terminal targets in the pathogenesis of RA [3,4]. Synovial hyperplasia, which contributes to the progression and development of RA, mainly results from the active proliferation and aggressive tumor-like characteristics of rheumatoid arthritis-broblast-like synoviocytes (RA-FLSs) [5,6].…”
Section: Introductionmentioning
confidence: 99%